"I am in a constant struggle:" The challenges of providing instruction to incarcerated youth in southern California. (July 2020) - Flores, Jerry; Barahona-Lopez, Kati
Abstract: This paper examines the challenges of mandatory educational instruction in the California correction system. Current scholarship on youth education in incarceration focuses on the challenges faced by youth and teachers. Our study adds to this scholarship by demonstrating that the context of teaching in centers of incarceration, specifically center of incarceration that have adopted a wraparound service strategy, prevents teachers from disentangling their teaching practices from practices of managing and disciplining youth who are in incarceration. Using semi-structured interviews, we interviewed 15 teachers who work in four juvenile detention facilities in Southern California. We found three primary challenges: one, low level of education; two, the emotional labor required of teachers; three, negotiating the interactions with administrators, correctional officers, and other on-site personnel. Thus, our findings demonstrate that the three challenges highlighted macro-institutional barriers which individual teacher and students are able to navigate but are unable to fundamentally change.